Structural analysis of VirD4 a type IV ATPase encoded by transmissible plasmids of Salmonella enterica isolated from poultry products - Gokulan, Kuppan; Khare, Sangeeta; Foley, Steven L. (Frontiers in Artificial Intelligence, 2022)
Bacterial species have evolved with a wide variety of cellular devices, and they employ these devices for communication, transfer of genetic materials and toxins. They are classified into secretory system types I to VI based on their structure, composition, and functional activity. Specifically, bacterial type IV secretion system (T4SS) is a more versatile system than the other secretory systems because it is involved in transfer of genetic materials, proteins and toxins to the host cells or other bacterial species. The T4SS machinery is made up of several proteins with distinct functions and forms a complex, which spans the inner and outer membranes. This secretory machinery contains three ATPases that are the driving force for the functionality of this apparatus. At the initial stage of the secretion process, the selection of substrate molecules and processing occurs at the cytoplasmic region (also known as relaxosome) and then transfer mechanism occurs through the secretion complex. In this process, the VirD4 ATPase is the first molecule that initiates substrate selection, which is subsequently delivered to the secretary machinery. In the protein data bank (PDB) no structural information is available for the VirD4 ATPase to understand the functional property. In this manuscript, we have modeled VirD4 structure in the Gram-negative bacterium Salmonella enterica and describe the predicted functional importance. The sequence alignment shows that VirD4 of S. enterica contains several insertion regions as compared to template structure (pdb:1E9R) used for homology modeling. Here, we hypothesize that the insertion region could play a role in flexible movement of hexameric unit during the relaxosome processing or transfer of the substrate.